POLISH HERITAGE OF VILNIUS BOOK STUDIES BETWEEN THE TWO WORLD WARS - ŁUSZPAK, AGNIESZKA (Knygotyra, 2015)
Although this is a comparatively new field, the world book science has its rich history. Just like Polish book science, which roots in the middle of the 18th century, when the first drafts on the history of printing and bibliography appeared. However only the achievements of Joachim Lelewel, the author of Two Bibliographic Books, set path for the whole generations of librarians and bibliologist. It was right in Vilnius were the first Polish book study theoretician published his Books. In this university town of great traditions definitely exists a genius loci, which prevailed for many centuries; it is visible in the creativity of such persons as Adam Łysakowski, Tadeusz Turkowski (who often used the nick name Jerzy Czarnecki), Ludwik Abramowicz or Michał Brensztejn. One of the outstanding individualities to develop the between World War librarianship and book study to a large degree was Łysakowski, the employee and head librarian of Vilnius University Public Library. His work The subject catalogue practically revolutionized the field of subject study in Poland. And with the engagement in publishing the work of Jan Ladislav Živny Handbook of Bibliography, Łysakowski popularized modern book study stream in Poland. He was also deeply interested in the matters of regional bibliography and printings statistics. During his stay in Vilnius, Łysakowski was also interested in educating the librarians and their professional status. Turkowski often emphasized that for many centuries in Poland Vilnius was the most important cultural centre next to the capital city (Cracow, then Warsaw). He postulated interest in the history of Vilnius science and education – he published monumental work called Materials to the History of literature and education in Lithuania and Russia from the Archives of Printing House and Józef Zawadzki Book shop in Vilnius from 1805 to 1865. Turkowski also published the articles on Vilnius booktrade and Vilnius book. The translation of the fore-mentioned Handbook of Bibliography was also his work. Abramowicz was a administrator of the Wróblewski Library. He had a rich collection of printings connected with Lithuania and Vilnius – his lithuanica, vilnensia and others were donated for public use. From his collection there was also created the Iconographic Museum in Vilnius. He also worked on regional bibliography of Great Principality of Lithuania. His work Four Centuries of Printing in Vilnius still remains one of the most important studies of this field. Vilnius librarian Brensztejn, although he lacked formal education, in 1936 was awarded for his contribution to science with the diploma honoris causa at the Vilnius University. He published 400 works on Lithuania history and ethnography and more than 20 in scope of bibliography, book history and libraries of this region. He organized exhibitions, which pictured the history of Vilnius University or Vilnius libraries. University Public Library, the Wróblewski Library, Society of Friends of Arts and Sciences or Vilnius Circle of Polish Librarians Association were the most important centers of bibliological scientific life in the period between two World Wars. It was there were fore-mentioned and many more book scientists ran their scientific and professional activity. Their writings perfectly document the history of book culture in Lithuania, and through their activity Łysakowski, Turkowski, Abramowicz and Brensztejn and others were engaged not only in pure librarian works, but also in social and scientific life of Vilnius. They often emphasized the many-year-standing duality of Poland, where Vilnius constituted the major centre of science and culture next to the capital city. Studying this area Vilnius librarians contributed in a large degree to the development of history of Polish and Lithuanian education, science and culture.